Penguatan Kesehatan Lingkungan Masyarakat Melakukan Kegiatan Penanaman Tumbuhan Sayur Dan Kebersihan Lingkungan - Mochamad Saleh; ahmad muqit murtadloh; Rahayu Mardikaningsih; Didit Darmawan; Ilmiyetul Chonimah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Environmental health is a key factor influencing people’s quality of life, yet low awareness of hygiene and the underutilisation of vacant land remain challenges. This Community Service Programme (PkM) aims to strengthen environmental health through vegetable planting and clean-up initiatives around Sunan Giri University in Surabaya. The method employed is Asset-Based Community Development (ABCD) to optimise local potential. The programme stages include planning, asset identification, outreach, planting activities, and joint environmental clean-ups involving students and local residents. The programme’s results demonstrate increased awareness and active community participation in maintaining cleanliness and utilising vacant land productively. In addition to improving physical conditions, these activities strengthen social bonds and foster a sense of shared responsibility. This PkM is expected to serve as a first step in promoting clean and healthy living habits to create a sustainable community environment.